IMPACT OF REMOTE WORK ON EMPLOYEES’ JOB SATISFACTION IN SOME SELECTED REMOTE COMPANIES IN NIGERIA - Chinedu Nnadozie, Charles (African Journal of Social and Behavioural Sciences, 2026)
The survey was conducted to assess the impact of remote work on job satisfaction. Given the importance of flexibility and technology in remote work, the study examines whether technology use increases employee stress and whether employees’ time management and work policies affect work-life balance in remote work companies in Nigeria. Primary and secondary sources of data where use to collect information for this study. A questionnaire was used to elicit information from 323 respondents who constitute the sample for this study. The data were analysed using the Chi-Square test to test the hypotheses formulated for the study. The findings revealed that poor technological support increases employee stress levels and that work policies affect employee autonomy. The study recommended that remote companies should provide their employees with effective technological tools to enable them to carry out their duties without stress, and formulate more favourable work policies that would enable employees to enjoy greater autonomy.